ENHANCING AUTOMATIC MULTIPLE NUMBER PLATE RECOGNITION: MODEL ARCHITECTURE, EVALUATION RESULTS, AND IMPLEMENTATION CHALLENGES (CAHIERS MAGELLANES-NS, 2024)
Number plate recognition (NPR) systems are crucial for vehicle theft prevention, traffic management, and law enforcement. Despite their importance, current methods struggle with accuracy, speed, and adaptability to different environments. This research presents a novel methodology to enhance these systems by maximizing accuracy and minimizing recognition time. Our approach employs advanced preprocessing techniques to streamline the recognition process, reducing unnecessary computations and boosting efficiency. It also ensures reliable recognition of multiple plates under varying backgrounds and lighting conditions, enhancing system versatility. Additionally, intelligent algorithms are integrated to halt processing when no plate is detected, conserving resources and time. Experimental results and comparative analysis with existing methods demonstrate that our approach significantly improves accuracy, efficiency, and adaptability, making it a robust solution for real-world NPR applications. The findings provide valuable insights and methodologies that have the potential to significantly enhance the performance and effectiveness of NPR systems in practical scenarios.